PERAN TRANSFORMATIONAL LEADERSHIP DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI DESA BAKAU ACEH KECAMATAN MANDAH - Reno Regen; Muhammad Fauzan; Ahmad Rifa'i (Indragiri Research Center (ingreat), 2026)
This study aims to analyze the role of transformational leadership in increasing community participation in Bakau Aceh Village, Mandah District. This research used a qualitative approach with a descriptive qualitative method. The population consisted of all village officials of Bakau Aceh Village totaling nine people. The research informants included the key informant, namely the Village Head, and supporting informants consisting of the Village Secretary, Head of Government Affairs, Head of General and Planning Affairs, and the Heads of Hamlet I, II, and III. Data analysis was conducted using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the transformational leadership of the village head contributes to increasing community participation at every stage of village development, including planning, implementation, utilization of development outcomes, and evaluation. The application of the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration fosters trust, a sense of ownership, and collective commitment among the community toward village development programs. Therefore, transformational leadership not only creates structural opportunities for participation but also encourages more active, conscious, and sustainable community involvement in village development.